Formulating PEO-polycarbonate blends as solid polymer electrolytes by solvent-free extrusion - Francesco Gambino; Matteo Gastaldi; Alia Jouhara; Samuel Malburet; Simone Galliano; Nicola Cavallini; Giovanna Colucci; Marco Zanetti; Alberto Fina; Giuseppe Antonio Elia; Claudio Gerbaldi (Journal of Power Sources Advances)
Liquid electrolytes are currently state-of-the-art for commercial Li-ion batteries. However, their use implicates inherent challenges, including safety concerns associated with flammability, limited thermal stability, and susceptibility to dendrite formation on the lithium metal anode, that can compromise the battery lifespan. Solid-state polymer electrolytes offer an alternative to conventional liquid electrolytes, aiming to mitigate safety, stability, and performance drawbacks. This study investigates the preparation and the comprehensive characterization of polyethylene oxide (PEO) and polycarbonate (PC) blends obtained through extrusion process. The process is solvent-free and easily scalable at the industrial level; it grants the efficient dispersion and mixing of PEO and PC. Blends at different ratios of PEO (Mw of 4 × 105 and 4 × 106 g mol˗1) and two types of PCs (namely, polyethylene and polypropylene carbonate) including lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are prepared. Optimization and investigation of the relative effects between the application of different PCs and the variable ratios of PEO/PCs on the mechanical, morphologic and electrochemical properties of the final polymeric membranes is carried out for future applications of these systems, as efficient electrolytes in all-solid-state lithium batteries.